Unveiling Earth's Hidden Magnetization - Vervelidou, Foteini; Lesur, Vincent (Geophysical research letters, 2018)
Rock magnetization carries information about rocks' properties, Earth's tectonic history, and evolution of its core magnetic field. One way to study Earth's magnetization is through the magnetic signal it generates, known as the lithospheric magnetic field. Although there exist global lithospheric magnetic field models of high spatial resolution, this path has not yet been very fruitful because of an important limitation: only part of the magnetization is visible, that is, produces an observable magnetic field signal. We refer to the remaining part of the magnetization as the hidden magnetization, and we recover it from a lithospheric magnetic field model under a few reasonable assumptions. We find that Earth's hidden magnetization at high and middle latitudes is very similar, both in intensity and shape, to Earth's visible magnetization. At low latitudes, the estimated hidden magnetization relies on a priori information and can be very different from the visible one. Plain Language Summary Earth's uppermost layer is abundant in magnetized rocks. Rocks' magnetization acts as a recorder of many processes taking place inside the Earth, from the crust down to the core, which lies almost 3,000 km far from the surface. Currently, the most common way to extract this information is through laboratory measurements of rock samples. An alternative way is to study the magnetic signal of magnetized rocks, which is known as the lithospheric magnetic field. This is measured by satellites orbiting around the Earth and airborne and marine missions. Inferring, however, the direction and the strength of the magnetization from magnetic field measurements is not straightforward. The reason is that a large part of a given magnetization generates no magnetic field. We call this part of the magnetization hidden as opposed to the remaining part, which we call visible. In this study, we show how the visible and the hidden parts of the magnetization are linked to each other. This link allows us to uniquely recover most of Earth's hidden magnetization. Recovering this part of Earth's magnetization enables a better link to the underlying processes, like crustal thickness contrasts, temperature gradients, hydrothermal activity, or deposits of highly magnetic minerals like magnetite. Key Points More than half of Earth's magnetization is hidden in the sense that it generates no observable magnetic field signal Under few reasonable assumptions, we uniquely recover most of Earth's hidden magnetization from a lithospheric magnetic field model Recovering the hidden part of Earth's magnetization enables a better link to the underlying internal processes